2009
DOI: 10.1111/j.1745-6606.2008.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Messages in Prime‐Time Television Series

Abstract: Alcohol messages contained in television programming serve as sources of information about drinking. To better understand the ways embedded messages about alcohol are communicated, it is crucial to objectively monitor and analyze television alcohol depictions. This article presents a content analysis of an eight-week sample of eighteen prime-time programs. Alcohol messages were coded based on modalities of presentation, level of plot connection, and valence. The analysis reveals that mixed messages about alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 60 publications
2
53
0
2
Order By: Relevance
“…Further, alcohol depictions and product placements in TV programming are common [41]. These depictions and product placements may reinforce alcohol advertisements.…”
Section: Traditional and Digital Exposure Venuesmentioning
confidence: 99%
“…Further, alcohol depictions and product placements in TV programming are common [41]. These depictions and product placements may reinforce alcohol advertisements.…”
Section: Traditional and Digital Exposure Venuesmentioning
confidence: 99%
“…Recent studies in the UK (Coyne & Ahmed, 2009), in New Zealand (McGee, Ketchel, & Reeder, 2007) and in the US (Russell & Russell, 2009) have added further confirmation to the general pattern of findings regarding television entertainment portrayal of alcohol and drinking. In a study of soap operas on British television, Coyne & Ahmed (2009) found that more than 90% of soap opera episodes depicted alcohol-related acts, with an average of 7.65 acts per episode.…”
Section: Broadcast Entertainmentmentioning
confidence: 55%
“…While numerous studies have noted that film and television programs portray both positive and negative images of alcohol and drinking, albeit with a distinct emphasis on positive images, the study by Russell and Russell (2009) is particularly noteworthy for showing that positive and negative portrayals are qualitatively different. Thus negative messages tend to be foregrounded and central to the narrative, while positive messages are invariably communicated as part of the 'normal' background.…”
Section: Broadcast Entertainmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, research from the National Television Violence Study concluded that much of the violence portrayed in TV was potentially risky for viewers because it was trivialized, glamorized, and sanitized. Additional research across different types of risk behaviors on TV on content, timing, and context of risk behaviors to extend the (somewhat contradictory) work already done 13,22,23 may elucidate the overarching messages that youth receive when behaviors are paired (or not).…”
Section: Figurementioning
confidence: 99%